2023
DOI: 10.1088/1755-1315/1135/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Co-digestion of food waste with cow dung by anaerobic digestion for biogas production.

Abstract: Food waste is categorized under household waste which were produce in large amount every day and it can be a good potential to generate biogas production via anaerobic digestion. In this research, the characteristics of co-digestion process are measured to determine the biogas production between food waste and cow dung. The food waste is co-digest with two different type of cow dung are collected depends on their food consuming (grass:bran); 100% grass and 95% grass : 5% bran. The digester is maintained at 35°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…TAN, which has an adverse effect on AD process, was also reduced when substrates mixed with inoculum. The addition of inoculum brought the C/N ratio of substrates in between 31.83 and 39.84, which is slightly higher than the optimum range (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). This might not cause any major impact as optimum range of C/N ratio may vary depending on the substrates from 9 to 50, as reported by Guarino et al [57].…”
Section: Characterization Of Substrate During Acodmentioning
confidence: 90%
See 1 more Smart Citation
“…TAN, which has an adverse effect on AD process, was also reduced when substrates mixed with inoculum. The addition of inoculum brought the C/N ratio of substrates in between 31.83 and 39.84, which is slightly higher than the optimum range (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). This might not cause any major impact as optimum range of C/N ratio may vary depending on the substrates from 9 to 50, as reported by Guarino et al [57].…”
Section: Characterization Of Substrate During Acodmentioning
confidence: 90%
“…Nowadays, researchers are focusing on ACoD due to its superiority [23][24][25]. Several studies showed that anaerobic co-digestion of cow dung with fruit waste [26], waste leaf [27], elephant grass [28], food waste [29], lignocellulosic crop residue [30], and aquatic waste [31], respectively, enhanced biogas and methane yield. Lignocellulosic crop residues contain a higher percentage of carbon; on the other hand, cow dung contains a higher percentage of nitrogen, so anaerobic co-digestion of these two wastes may be best suited for nutrient balancing and enhancing biogas yield from cow dung.…”
Section: Introductionmentioning
confidence: 99%
“…In tandem, vegetable waste generated from agricultural, culinary, and processing activities contributes to the growing organic waste burden [19]- [22]. The global adoption of anaerobic co-digestion as a means to co-process these substrates signify a paradigm shift towards circular economy principles, wherein organic waste is transformed into a valuable resource [23], [24]. This research paper aims to know the best ratio of pressmud and vegetable waste in anaerobic co-digestion and its impact on biogas production efficiency and waste management practices.…”
Section: Introductionmentioning
confidence: 99%